A new genus and species of American Parmenini, and notes on Estola freyi Breuning (Desmiphorini) (Coleoptera, Cerambycidae, Lamiinae) - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2022)
A new genus and species of Parmenini, Parmakanthion profundum, from Honduras is described and illustrated. Estola freyi Breuning, 1955 is illustrated for the first time and some features allowing to recognize it are provided.